DETERMINATION OF FACTORS EFFECTING ACHIEVEMENT OF THE TARGET BLOOD PRESSURE LEVEL IN PATIENTS WITH ARTERIAL HYPERTENSION AFTER THE ELECTRIC CARDIAC PACEMAKER IMPLANTATION - Deriyenko, T.A.; Shop, I.V.; Tykhonova, T.M.; Glavatskih, T.S.; Levadna, Yu.V.; Shepitko, K.V. (World of Medicine and Biology, 2020)
The total of 119 patients (62 men and 57 women) aged 69.5±11.6 were observed at the one-year stage of maintenance drug therapy after implantation of electric cardiac pacemaker in DDD / DDDR, VVI / VVIR modes. Patients were divided into 3 groups with 1, 2 and 3 grades arterial hypertension. To determine the factors affecting the achievement of target blood pressure in patients with arterial hypertension after implantation of a pacemaker, potential factors that could be associated with achieving blood pressure control were compared. They were identified using univariate log-regression analysis and multivariate log-regression analysis. The results showed that the frequency of reaching the office arterial pressure, BP
Keywords: arterial hypertension; cardiac pacing; correlation